The Effect of Lighting on Unsafe Conditions at PT. X - Setyowati, Wulan; Inayah, Zufra (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
Occupational Safety and Health (OHS) is an important component in supporting protection for workers. Lighting is an essential physical element in the implementation of the Occupational Safety and Health (OHS) program. Light intensity that does not meet standards can cause visual fatigue, decrease worker concentration levels, and increase the risk of unsafe conditions in the workplace. This study aims to determine the effect of lighting on unsafe conditions at PT. X. This study uses a quantitative approach with a cross-sectional design, involving 80 respondents who were randomly selected using a simple random sampling technique. Data were collected through observation and questionnaires, then analyzed using a simple logistic regression test assisted by SPSS software. The results showed a statistically significant relationship between lighting and unsafe conditions (p = 0.002). Workers who work in areas with lighting levels that do not meet standards are 4.95 times more likely to experience unsafe conditions compared to those who work in areas with lighting according to regulations (Exp(B) = 4.951). Based on these findings, it is concluded that non-standard lighting significantly affects the occurrence of unsafe conditions, so it is necessary to adjust the lighting intensity in accordance with the Regulation of the Minister of Manpower No. 5 of 2018 in order to create a safer and more comfortable working environment.